PERFORMANCE ANALYSIS OF SIGNALIZED INTERSECTIONS ON JL. SOEKARNO HATTA, JL. MT. HARYONO, AND JL. MAYJEND PANJAITAN WITH SOFTWARE PTV VISSIM 9 AND MKJI 1997 METHOD - Pranoto, Riski Ainurrohmah (BANGUNAN, 2021)
Abstract: The higher population growth makes the community's need for transportation facilities and infrastructure also higher. One of the intersections that is always crowded with vehicles from various directions, especially during rush hours on weekdays in Malang is the Jl. Soekarno Hatta due to the increase in the volume of vehicles from year to year. In addition, the traffic light at the intersection of Jl. MT. Haryono has been disabled by engineering traffic for motorists going to Jl. Mayjend Panjaitan was required to turn back on Jl. Soekarno Hatta first. This causes vehicle queues, delays, and congestion on Jl. Soekarno Hatta at certain hours which resulted in longer travel times. This study aims to (1) describe the results of the evaluation of the performance of the signalized intersection software PTV Vissim 9 and MKJI 1997, (2) describe the performance of the signalized intersection for the next 5 years, (3) plan alternative solutions to the problems that occur at the signalized intersection in the existing condition. This research method refers to the analysis of MKJI 1997 and PTV Vissim 9 which is used to obtain the existing saturated condition which will later be used as a reference for calculating the prediction of intersection performance in the next 5 years and as a reference in planning alternative solutions that allow to improve the performance of the signalized intersection. Based on the results of the study, it is known that (1) the performance of the existing condition is very saturated where at the intersection of Jl. Soekarno Hatta DS value 0.945, while Jl. Mayjend Panjaitan DS value of 0.945. The average delay is 36.75 sec/pcu category D. Vissim's calculation is 62.58 sec/veh with category E. (2) Prediction of intersection performance in the 5th year obtained a delay value of 37.51 sec/pcu category D for existing conditions. (3) Alternative solutions that allow to improve intersection performance include alternative 2 adding phases, movement, and widening the road with a DS value of 0.872 for all approaches, an average delay of 22.97 sec/pcu category C. Vissim's calculation obtained 72.64 sec/veh with category E. Alternative 4 is the addition of underpass with a DS value of 0.879 for all approaches, the average delay is 22.77 sec/pcu category C. Predicted performance in the 5th year obtained a delay value of 23.32 sec/pcu category C for alternative 2 and 22.90 sec/pcu category C for alternative 4. It is known that alternative 4 solution allows to improve the performance of signaled intersections, this can be seen in the delay obtained.Keywords: performance of intersection, signalized intersection, MKJI, vissim